Áreas prioritárias para a conservação do peixe-boi marinho Trichechus manatus no Ceará e Rio Grande do Norte - Choi, Katherine Fiedler (2011)
In this study, it was addressed priorities areas for the conservation of the Antillean Manatee,Trichechus manatus manatus, on the east coast of Ceará and the west coast of Rio Grande do Norte states. Setting priority areas for conservation is extremely important to direct efforts and design actions to avoid species and ecosystems extinction and ensure ecological services. The Antillean Manatee, Trichechus manatus manatus, is the most endangered marine mammal of Brazil. Current population estimative ranges between 200 to 500 animals,showing signals of decline. Classified as “CR” in the Brazilian Red List and “EN” in the IUCN Red List, the species is a high priority conservation target in the country. The west coast of Rio Grande do Norte (RN) and the east coast of Ceará state (CE) comprises the major area of manatee calves’ strandings, the mainly threat to the species. This work gathered basic information about the occurrence and distribution of the species in this key region, important areas of use, like feeding areas, freshwater sources and nursing area and the threats and human impacts on the species, in order to determine priority areas for manatee conservation. The methodology was adapted from The Nature Conservancy (“Priority Setting Step of Conservation by Design”), which identifies high priority places and ensure biodiversity conservation. The study area is located between Beberibe city (CE) and Touros city (RN), with 500km of extension, divided in 83 coastal communities, with the presence of six estuaries. Each community was analyzed separately, according to the presence of manatee ecological attributes, i.e., manatee occurrence, presence of seagrass meadows, freshwater sources and birth areas. Also, these attributes were classified according to its current condition, vulnerability and abundance. Data gathered produce a ranking of the communities, with an asymmetric continuum between suitable areas and those with absence of any of the ecological attributes. Results demonstrated that 50,6% of the communities has a high level of ecological importance for the species. A map with priority areas for manatee conservation was elaborated, with blocks of different priority levels distributed in the study area, between extremely high, very high and high priority areas. The coast between eastern of Aracati (CE) and western of Icapuí (CE), Areia Branca coast (RN) and São Miguel do Gostoso and Touros coast (RN) are the highest priorities areas for manatee conservation in the region. They all have manatee ecological attributes, but differ on the intensity of threats, which should address different strategic actions in each local. The next step to the Antillean Manatee conservation plan in the area will be identification of priority actions, time scale and actors, addressing them for each community studied, according to manatee threats and degree of priority.